Pemilihan Supplier Pakan Ternak Ayam pada PT X Menggunakan Metode Analytical Hierarchy Process (Ahp) - Kristiani Margaretta Harianja; Ni Luh Dian Purnami; Anak Agung Gede Weda Baweswara; Sang Putu Aris Wesnawa; Rifandya Salwadita Mahendra (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The supply chain is crucial to company operations, especially in the poultry farming industry, to ensure the availability of quality feed. PT X, located in Kintamani, faces challenges in its supply chain due to the long distance from its main supplier, PT Sreeya Sewu. This has led to high logistics costs and risks of delivery delays, which impact the company’s operational efficiency. This study aims to assist PT X in selecting the best supplier using the Analytical Hierarchy Process (AHP) method and the Super Decision application. With five criteria and 15 sub-criteria, the results show that UD Tunas Harapan is the best supplier, excelling in nine sub-criteria.